Free Flap Versus Pedicled Flap Reconstruction of Laryngopharyngeal Defects: A 10‐Year National Surgical Quality Improvement Program Analysis. (27th August 2018) - Haidar, Yarah M.; Kuan, Edward C.; Verma, Sunil P.; Goddard, Julie A.; Armstrong, William B.; Tjoa, Tjoson
Abstract : Objectives/Hypothesis: Large defects after total laryngectomy (TL) and total laryngopharyngectomy (TLP) often benefit from free flap (FF) or pedicled flap (PF) reconstruction to maintain continuity of the aerodigestive tract, protect great vessels, or reinforce pharyngeal closure. Although both techniques are commonly used, no consensus exists as to which results in fewer complications. The goal of this study was to determine if 30‐day morbidity/mortality outcomes differ between PF and FF reconstruction in patients undergoing TL/TLP. Study Design: Retrospective cohort study. Methods: Patients were analyzed who underwent TL/TLP with reconstruction using records from the American College of Surgeons National Surgical Quality Improvement Program database (2005–2015). Results: A total of 347 patients were included; 204 received FF reconstruction, whereas 143 received PF reconstruction. FF reconstruction was more commonly used with TLP defects ( P  = .001). The total operative time in the FF (590 ± 140 minutes) was longer than the PF (441 ± 125 minutes) group ( P  < .0001). There was a higher rate of postoperative transfusions in those undergoing FF reconstruction ( P  = .022). There was no significant difference in complication rates among TLP patients. Among TL patients only, FF reconstruction had a higher association with wound infections than PFs ( P  = .040). On multivariate analysis, low hematocrit was associated with complications ( P  = .031). Age ( P  = .031) and congestive heart failure exacerbation ( P  < .001) were associated with increased hospital stay. Overall, there were no differences in readmissions, reoperations, or deaths between the groups. Conclusions: Reported complication rates after TL/TLP remain high, despite widespread usage of vascularized flaps in reconstruction. This comparison reveals no significant difference in postoperative complications between patients who received PF and FF laryngopharyngeal reconstruction. Level of Evidence: 4 Laryngoscope, 129:105–112, 2019